The Effective of Policy in Karawang Regency Towards Change Profession in Sirnabaya Village, East of Telukjambe District - Prihatini, Juliati; Zulaika, Siti (International Journal of Applied Business and International Management, 2022)
The purpose of this study is to analyze the effectiveness of the Karawang Regency Government Policy in transferring livelihoods in Sirnabaya Village, Telukjambe Timur District. The research method uses a qualitative descriptive type of research. Data collection techniques through observation, structured interviews and documentation. The results showed that the local government's policy towards less productive land, allocated into industrial estates, was very effective. The local government through the Job Training Center at the Manpower and Transmigration Office in collaboration with companies, and private educational and training institutions in order to provide solutions through improving the skills of the workforce that transfers livelihoods aims to accommodate 60% of the local workforce in the company. The policy is very effective in reducing the number of unemployed. However, the company's restrictions on workers aged 18-20 are contrary to the law that says that age is the productive age, therefore it needs to be reviewed. The findings of this study the authors suggest that the age of 20-year-old employees is the productive age, companies should not make dismissals at that age. The determination of the productive age should refer to the provisions carried out by the Manpower and Transmigration Service.Â Keywords: effectiveness, proportion of labor, wages